Keterkaitan Antara Fenomena Upwelling dan Jumlah Tangkapan (Hook Rate) Tuna di Perairan Selatan Pulau Jawa-Bali - Ibadur Rahman; Kunarso Kunarso (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2022)
The upwelling area is very potential tuna fishing ground. This area is very rich in nutrients and has a high fishery productivity, thus will trigger the arrival of tuna to find food in the area. The arrival of tuna in the upwelling area occurs through a food chain process (phytoplankton – small herbivorous fish – small carnivorous fish – tuna). This study aims to examine the correlation between upwelling and tuna hook rate. Upwelling area data were obtained from MODIS chlorophyll-a concentrations data which were processed using SeaDAS and ArcGIS software, while tuna catch data were obtained from the catch logbook belonging to P.T. Perikanan Nusantara, Benoa, Bali. The relationship between the upwelling and tuna hook rate was analyzed using the Pearson correlation test. The test results showed that the upwelling and hook rate of tuna had a correlation of 0.589 (n = 13), indicating that the upwelling had a strong influence on the hook rate of tuna at the southern waters of Java-Bali.